The Expanding Therapeutic Perspective of CCR5 Blockade - Luca Vangelista, Sandro Vento (My University, 2018)
CCR5 and its interaction with chemokine ligands have been crucial for understanding HIV‑1 entry. Over time, CCR5 shifted from being considered minor to becoming central in multiple pathophysiological conditions. Therapeutic efforts targeting CCR5—including CCR5Δ32 mutation studies, gene editing, small molecules, antagonist antibodies, and engineered chemokine ligands—may serve as paradigms for treating a wide array of diseases. CCR5, broadly expressed across cell types, plays a key role in directing immune cell trafficking during inflammation. Beyond HIV‑1, CCR5 is implicated in cancer, atherosclerosis, inflammatory bowel disease, multiple sclerosis, and others. Naturally CCR5Δ32 homozygotes are healthy yet resistant to HIV, which has inspired therapeutic strategies. The mini-review discusses antagonism or gene-editing-based CCR5 blockade as potential approaches to mitigate progression or severity across these diseases
Keywords: CCR5; CCL5; HIV-1; cancer; inflammation; therapeutic blockade